(untitled) (Clepsidra - Interdisciplinary Journal of Memory Studies, 2022)
How to look at a space of disappearance? How to photo- graph a clandestine detention centre? How to narrate the facts of which these walls have witnessed? And finally, how to retrace from the surviving marks to the testimony? From these questions, this presentation explores the possibility of testimony about argentinian recent past, based on one of the photographs of Paula Luttringer’s El lamento de los muros. In this work, the artist links image and writing as a starting point for a reconstruction of meaning, as an act that may give voice to the victims.